2020
DOI: 10.1002/slct.202002869
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Metallic Nanoparticles Stabilization in Water by Imidazolium Salts: A Complete Physicochemical Study

Abstract: We present the total characterization (by UV-Vis spectroscopy, Transmission Electron Microscopy, Dynamic Light Scattering, Zeta potential, Fourier Transform Infrared Spectroscopy, and Nuclear Magnetic Resonance) of silver nanoparticles (Ag-NP) together with an exhaustive physicochemical study about the role of sulfonated imidazolium salts in their stabilization. Our results show how the orientation of the sulfonated imidazolium salts and the interaction of the hydrocarbon chain with the Ag-NP surface are respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In this way, we have demonstrated that the imidazolium salts interact electrostatically through the imidazole ring with the metal surface. However, the arrangement acquired by the stabilizers on the MNPs and the interaction of the hydrocarbon chain with the metal surface (Au or Ag) is different in each case [24,25] . On the other hand, the fact that the AgNP and AuNP stabilized with L3 present the highest k values suggests some specific interaction of this ligand with the metal surface, which increases the catalytic activity of the MNPs.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In this way, we have demonstrated that the imidazolium salts interact electrostatically through the imidazole ring with the metal surface. However, the arrangement acquired by the stabilizers on the MNPs and the interaction of the hydrocarbon chain with the metal surface (Au or Ag) is different in each case [24,25] . On the other hand, the fact that the AgNP and AuNP stabilized with L3 present the highest k values suggests some specific interaction of this ligand with the metal surface, which increases the catalytic activity of the MNPs.…”
Section: Resultsmentioning
confidence: 97%
“…Also, the geometry of AgNP influences the catalytic efficiency. The fact that 3 is irregular in shape, and that it is added in a small cluster, [25] would explain the greater catalytic power compared to 1 and 2 , respectively. All these facts carry out us to confirm that 3 is the best system to be used as a catalyst in homogeneous medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…40 The different λ max obtained could be suggesting that the size, growth, and, collective dipole oscillations of Au-free electrons depend on the stabilizing matrix chemical nature used in the synthesis. 41 The hydrogel's different chemical properties depend on the monomer's chemical structure, which affects the nanomaterial optical properties incorporated into the hydrogel. In addition, the absence of an important shift of the maximum absorbance peak suggests a good Au-NPs dispersion within the hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…According to Mie's theory,39 there is a relationship between SPR maximum and size, the Au-NPs are smaller when there is a hypsochromic shi in the SPR maximum 40. The different l max obtained could be suggesting that the size, growth, and, collective dipole oscillations of Aufree electrons depend on the stabilizing matrix chemical nature used in the synthesis 41. The hydrogel's different…”
mentioning
confidence: 99%